Pendekatan E-Readiness Untuk Mengukur Tingkat Kesiapan Adopsi E-Marketplace Bagi UMKM di Provinsi Bengkulu: Pendekatan E-Readiness Untuk Mengukur Tingkat Kesiapan Adopsi E-Marketplace Bagi UMKM di Provinsi Bengkulu - Arifah Hidayati; Yulperius Yulperius (International Journal of Management and Business (IJMB), 2021)
The purpose of this study is to analyze the readiness of e-marketplace adoption by MSMEs in Bengkulu Province. The method used is the e-readiness method using six indicators, namely Awareness, Human Resources, Business Resources, Technology Resources, Commitment and Governance. The research sample is MSMEs in Bengkulu Province and have criteria that have or are still using e-marketplace technology. Data collection was carried out through purposive sampling method. Variables were tested through Structural Equation Modeling (SEM) using Software SmartPLS. The measurement results show that e-readiness affects the level of readiness to use information technology facilities to sell their products through the e-marketplace. Based on the indicators used, the results show that the awareness indicator value is 3.45, the governance indicator value is 2.94, the commitment value is 2.94, the business resource value is 0.81, the human resource value is 2.60, and the technology resource value is 2.97. adoption rate value 3.11. The results show that the value obtained is at a sufficiently ready level for e-marketplace adoption